CHARACTERISTICS OF SMOKED CATFISH MINCED JERKY (Pangasius hypophthalmus) WITH FLAVOR VARIANTS - Mariani Harahap; N Ira Sari; Syahrul Syahrul (Berkala Perikanan Terubuk, 2021)
This study aims to determine the characteristics of smoked catfish minced jerky with flavor variants. The treatments given consisted of D1 (jerky without adding brown sugar and chilies), D2 (jerky with the addition of 10% coconut brown sugar) and D3 (jerky with 10% addition of green chilies). The analysis parameters observed were organoleptic test (appearance, aroma, texture and taste), chemical test (moisture, protein, fat, ash content) and Total Plate Count test. Smoked Catfish Minced Jerky with 10% addition of green chilies was most favored by consumer acceptance with 46 panelists (57.5%), with characteristics of appearance (dark brown), aroma (typical jerky and spicy aroma of green bird's eye chilies), texture (crispy and compact), and taste (savory and spicy). The average value of moisture, protein, fat, ash, and Total Plate Count was 10.94%, 21.19%, 2.30%, 0.46%, 6.7×103 colonies/g, respectively.